Deleterious mutation in the FYB gene is associated with congenital autosomal recessive small‐platelet thrombocytopenia. (25th May 2015) - Levin, C.; Koren, A.; Pretorius, E.; Rosenberg, N.; Shenkman, B.; Hauschner, H.; Zalman, L.; Khayat, M.; Salama, I.; Elpeleg, O.; Shalev, S.
Summary Background The FYB gene encodes adhesion and degranulation‐promoting adaptor protein (ADAP), a hematopoietic‐specific protein involved in platelet activation, cell motility and proliferation, and integrin‐mediated cell adhesion. No ADAP‐related diseases have been described in humans, but ADAP‐deficient mice have mild thrombocytopenia and increased rebleeding from tail wounds. Patients and methods We studied a previously reported family of five children from two consanguineous sibships of Arab Christian descent affected with a novel autosomal recessive bleeding disorder with small‐platelet thrombocytopenia. Homozygosity mapping and exome sequencing were used to identify the genetic lesion causing the disease phenotype on chromosome 5. Bone‐marrow morphology and platelet function were analyzed. Platelets were characterized by scanning electron microscopy. Results We identified a homozygous deleterious nonsense mutation, c.393G>A, in FYB. A reduced percentage of mature megakaryocytes was found in the bone marrow. Patients' platelets showed increased basal expression of P‐selectin and PAC‐1, and reduced increments of activation markers after stimulation with ADP, as detected by flow cytometry; they also showed reduced pseudopodium formation and the presence of trapped platelets between the fibrin fibers after thrombin addition, as observed on scanning electron microscopy. Conclusions This is the first report of a disease caused by an FYB defect in humans, manifested by remarkable small‐platelet thrombocytopenia and a significant bleeding tendency. The described phenotype shows ADAP to be important for normal platelet production, morphologic changes, and function. It is suggested that mutation analysis of this gene be included in the diagnosis of inherited thrombocytopenia.